The Role of Student Worksheets in Deep Learning-Based Inquiry Learning Models in Physics Education: A Systematic Literature Review - Jihan Defina; Phakrur Razi; Hufri Hufri; Hayyu Yumna (Physics Learning and Education, 2026)
Physics learning in schools is expected to facilitate not only the acquisition of conceptual knowledge but also the development of students’ scientific reasoning and higher-order thinking skills. One learning strategy that has gained attention in physics education is inquiry-based learning, particularly when supported by appropriate instructional materials. Student Worksheets play an important role in guiding students through structured learning activities that encourage active engagement and conceptual construction. In addition, the deep learning approach emphasizes meaningful learning, reflection, and the integration of knowledge across concepts. This study aims to systematically examine the role of Student Worksheets within inquiry-based learning models that are integrated with a deep learning approach in physics education. A Systematic Literature Review (SLR) was conducted by analyzing 15 relevant national and international journal articles published over the last ten years. The findings indicate that inquiry-based Student Worksheets designed according to deep learning principles contribute positively to students’ conceptual understanding, critical thinking skills, and learning engagement in physics. These results highlight the potential of integrating inquiry learning and deep learning approaches through well-designed Student Worksheets to enhance the quality of physics learning.